2009
DOI: 10.4161/cc.8.9.8314
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the transcription factor Yin Yang 1 in cancer development and progression

Abstract: The Yin Yang 1 (YY1) transcription factor has a pivotal role in normal biological processes such as development, differentiation, replication and cell proliferation exerting its effects on a huge number of genes involved in these processes. Mechanisms of YY1 action are related to its ability to initiate, activate, or repress transcription depending upon the context in which it binds. The role of YY1 played in cancer has been recently explored. This article summarizes the most relevant studies focused on YY1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 49 publications
(62 reference statements)
4
93
0
Order By: Relevance
“…2 In absence of certified cell lines from various normal tissues, two preparations of normal fibroblasts were used for comparison. As shown in the representative experiment reported in Figure 2B high YY1 protein expression was observed in the majority of cells lines (A274, A375, CAKI-1, CAKI-2, HT1080, MCF-7, HT-29, HS913T, Currently, DLBCL may be cured in a significant percentage of patients, depending on the initial characteristics of the tumor and the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In absence of certified cell lines from various normal tissues, two preparations of normal fibroblasts were used for comparison. As shown in the representative experiment reported in Figure 2B high YY1 protein expression was observed in the majority of cells lines (A274, A375, CAKI-1, CAKI-2, HT1080, MCF-7, HT-29, HS913T, Currently, DLBCL may be cured in a significant percentage of patients, depending on the initial characteristics of the tumor and the host.…”
Section: Discussionmentioning
confidence: 99%
“…By gene expression analysis of publicly available datasets from 9 different oncotypes for a total of 552 cancer samples and 276 normal samples, we recently observed that, in several tumor types, YY1 transcript levels were higher when compared to those of the normal counterparts. 2 However, YY1 involvement in hematopoietic malignancies, such as NHL, remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As named, YY1 can activate or inactivate gene expression depending on its interacting partners and functions as a master of the epigenetic regulatory network. 1 Overexpression of YY1 is observed in various cancers, such as prostate cancer, ovarian cancer, and colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…YY1 is known to have an important role in many biological processes; however, its function in cancer remains controversial (Park and Atchison, 1991;Shi et al, 1991Shi et al, , 1997Gordon et al, 2006;Castellano et al, 2009). Because YY1 positively regulates expression of several oncogenes, that is, E6 and E7, c-Myc, c-Fos and ErbB2 (Riggs et al, 1993;Lee et al, 1995a, b), and negatively regulates p53 stability (Gronroos et al, 2004;Sui et al, 2004), it is believed that YY1 acts as an oncogene (Gordon et al, 2006;Castellano et al, 2009).…”
Section: Yy1 Activates Brca1 Transcription M-h Lee Et Almentioning
confidence: 99%
“…YY1 is a multifunctional protein and is involved in both repression and activation of many genes that have a role in various important biological processes (Shi et al, 1997;Gordon et al, 2006;Castellano et al, 2009). It was shown that YY1 positively regulates expression of several oncogenes, including E6 and E7, c-Myc, c-Fos and ErbB2 (Riggs et al, 1993;Lee et al, 1995a, b).…”
Section: Introductionmentioning
confidence: 99%